In vitro regeneration and multiplication of borneo's endemic orchid phalaenopsis - Jill Sela Roja, Entalai. (Universiti Malaysia Sarawak (UNIMAS), 2015)
Orchids are the second largest families of flowering plant after sunflowers families. Phalaenopsis and Vanda are the most popular orchids as potted plant and cut flowers across the world. Both of these species are endemic to Borneo and have been listed as endangered species. In vitro propagation is the technique used in this study. The objective of this study was to determine the effects of plant growth regulators and organic additives on multiplication of Phalaenopsis and Vanda orchids. The protocorms of Vanda dearei was cultured on½ MS media with the supplement of plant growth regulators, NAA and BAP and organic compound, coconut water, potato homogenate and banana homogenate at different concentrations. Between NAA and BAP, 0.5 mg/L of NAA has shown the most effective proliferation ofprotocorm with an average of 11.72. For organic additives, the most effective proliferation of protocorm was 15% of coconut water with an average of 8.32 number of new protocorms formed. For Phalaenopsis bellina, explants were culture on NAA, BAP and TDZ at different concentration, only 1.0 mg/L of TDZ has shown spherical like body formed after 12 weeks of culture.